Eksploitasi Pekerja Migran dalam Persiapan Piala Dunia FIFA 2022 di Qatar: Antara Reformasi dan Realitas - Zainuddin, Kusmawardany; Ghazali, Imam (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2025)
Abstract Qatar’s appointment as a host of the 2022 FIFA World Cup brought global attention not only to the splendor of the sporting event, but also to the issue of exploitation of migrant workers involved in infrastructure development. This research aims to identify the forms of exploitation experienced by migrant workers, evaluate the effectiveness of labor reforms undertaken by the Qatari government, and assess FIFA’s responsibility and the role of the international community in addressing this issue. Using a descriptive qualitative approach and desk study analysis of reports from international organizations and credible media, the research is grounded in three main theoretical frameworks: global inequality (dependency theory), structural power theory, and human rights in the context of global citizenship. The results of this study show that although Qatar has claimed to reform, exploitation practices such as wage delays, dangerous working conditions, and restrictions on freedom still occur systematically. The reforms carried out tend to be normative and are not accompanied by effective supervision and law enforcement. Meanwhile, FIFA and the international community have not shown a strong commitment to ensure the protection of workers’ rights. This research emphasizes the need for deeper structural reforms and accountability from international institutions to prevent similar exploitation in the future. Abstrak Penunjukan Qatar sebagai tuan rumah Piala Dunia FIFA 2022 membawa sorotan global tidak hanya pada kemegahan ajang olahraga tersebut, tetapi juga pada isu eksploitasi pekerja migran yang terlibat dalam pembangunan infrastruktur. Penelitian ini bertujuan untuk mengidentifikasi bentuk-bentuk ekspolitasi yang dialami pekerja migran, mengevaluasi efektivitas reformasi ketenagakerjaan yang dilakukan oleh pemerintah Qatar, serta menilai tanggung jawab FIFA dan peran komunitas internasional dalam menangani permasalahan ini. Dengan menggunakan pendekatan kualitatif deskriptif dengan analisis studi literature dari laporan organisasi internasional dan media kredibel, penelitian ini berpijak pada tiga kerangka teori utama: ketimpangan global (dependency theory), kekuasaan struktural (structural power theory), dan hak asasi manusia dalam konteks kewarganegaraan global. Hasil kajian menunjukkan bahwa meskipun Qatar telah mengklaim melakukan reformasi, praktik eksploitasi seperti keterlambatan upah, kondisi kerja berbahaya, hingga pembatasan kebebasan masih terjadi secara sistemik. Reformasi yang dilakukan cenderung normatif dan tidak diiringi dengan pengawasan serta penegakan hukum yang efektif. Sementara itu, FIFA dan komunitas internasional belum menunjukkan komitmen yang kuat dalam menjamin perlindungan hak kerja. Penelitian ini menegaskan perlunya reformasi struktural yang lebih mendalam dan akuntabilitas dari lembaga internasional untuk mencegah eksploitasi serupa di masa mendatang.